Dietary diversity and food security in South Africa: an application using NIDS Wave 1 - Thornton, Amy Julia (School of Economics, 2016)
South Africa is food secure at the national level; however widespread food insecurity persists at the household level. To understand the dynamics of micro-level food insecurity this dissertation investigates how two different aspects of 'food access' - diet quality and diet quantity - affect two outcomes of 'food utilisation' - hunger and nutrition. Diet quantity is captured by food expenditure in Wave 1 of the National Income Dynamics Study (NIDS). To capture diet quality I use dietary diversity, which is not directly available in NIDS. I build and test a food group dietary diversity score and a food variety dietary diversity score using NIDS Wave 1. Both dietary diversity indicators are found to usefully summarise information about food security in South Africa by using methods found in the dietary diversity literature. The dissertation then turns to testing whether the theoretical differences between diet quality and quantity play out empirically in the case of nutrition (adult BMI) and hunger (self-reported household hunger). The results reveal that food variety and food quantity are complementary in explaining the chance of household hunger, with food quantity having a slightly more important effect. The pathways to BMI differ by gender. Dietary diversity and food expenditure are substitutes in the case of male BMI; however, food variety and food expenditure are complementary to explaining female BMI when food expenditure enters into the model as a quadratic. Overall, food variety proved to be a stronger and more significant correlate of both outcomes than the food group dietary diversity score.